(untitled) (Advances in Civil and Architectural Engineering, 2021)
This study examined steel and aluminum variants of modern exhibition structures in which the main design requirements include low weight (increased span/depth ratio, transportation, and construction) and durability (resistance to corrosion). This included a design situation in which the structural application of aluminum alloys provided an extremely convenient and practical solution. Viability of an aluminum structure depends on several factors and requires a detailed analysis. The overall conclusion of the study indicated that aluminum can be used as a structural material and as a viable alternative to steel for Croatian snow and wind load values and evidently in cases in which positive properties of aluminum are required for structural design. Furthermore, a structural fire analysis was conducted for an aluminum variant structure by using a zone model for realistic fire analysis. The results suggested that passive fire protection for the main structural members was not required in the event of areal fire with duration of 60 min.